2021
DOI: 10.2486/indhealth.2021-0119
|View full text |Cite
|
Sign up to set email alerts
|

Working from home: Cognitive irritation as mediator of the link between perceived privacy and sleep problems

Abstract: Since the COVID-19 pandemic began, many employees have been required to work full- or part-time at home. This paper investigates the impact of perceived privacy on cognitive irritation and sleep problems among employees who worked from home during the pandemic. Additionally, we analyzed the role of cognitive irritation as a mediator between privacy and sleep problems. We created a cross-sectional questionnaire, which was completed by 293 employees who performed home-based telework in German-speaking Switzerlan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 49 publications
4
11
0
Order By: Relevance
“…Since the public lockdown forced most employees to start mandatory working from home and effectively distanced themselves socially for a long time, the blurred boundary between work and private life would be created 11) . Over time, there are two types of job strain: cognitive and emotional strain 36,37) . Specifically, a perceived imbalance between private life and work pressure (i.e., lack of psychological detachment from work) would increase cognitive and emotional strain of teleworkers 36,37) , thereby intensifying the job demands.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the public lockdown forced most employees to start mandatory working from home and effectively distanced themselves socially for a long time, the blurred boundary between work and private life would be created 11) . Over time, there are two types of job strain: cognitive and emotional strain 36,37) . Specifically, a perceived imbalance between private life and work pressure (i.e., lack of psychological detachment from work) would increase cognitive and emotional strain of teleworkers 36,37) , thereby intensifying the job demands.…”
Section: Discussionmentioning
confidence: 99%
“…Over time, there are two types of job strain: cognitive and emotional strain 36,37) . Specifically, a perceived imbalance between private life and work pressure (i.e., lack of psychological detachment from work) would increase cognitive and emotional strain of teleworkers 36,37) , thereby intensifying the job demands. Moreover, as suggested by Fosslien and Duffy 38) , long-time video conferencing may trigger a new hurdle to teleworkers, namely "Zoom fatigue", a phenomenon of emotional strain 38) .…”
Section: Discussionmentioning
confidence: 99%
“…A lower distractibility in WFH compared to working on-site may point to more privacy during WFH. A recent study on the role of privacy in WFH showed a significant indirect effect of the level of privacy in WFH via cognitive irritation, indicating a lack of detachment from work issues, resulting in sleeping problems ( Wütschert et al, 2021 ). Hence, distractibility in WFH in relation to work on-site is not only closely linked to productivity but—as a proxy to privacy in WFH and work on-site—also to recovery from work.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of COVID-19 teleworking, there is some evidence that teleworkers experience privacy-related advantages, such as better concentration, resulting in increased efficiency, greater productivity ( Pfnür et al, 2021 ), and reduced occupational stress (e.g., Baert et al, 2020 ). Further, other research ( Ipsen et al, 2020 ; Xiao et al, 2021 ; Wütschert et al, 2021 ) points to differences in work privacy fit at home across samples. For example, the item “getting distracted by people at home” was identified for some as an aspect that negatively affected telework during the pandemic, whereas for others the items entitled “getting time to focus on my work without interruptions by other people” and “don’t have anyone watch[ing] me” were positive aspects of telework in comparison to office work ( Ipsen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 95%